MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMP NEGERI 26 PADANG DENGAN MENGGUNAKAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING - Islamirna Islamirna (Jurnal Edukasi dan Penelitian Matematika, 2018)
Tthe ability of understanding mathematical concepts of grade VII students of SMPN 26 Padang is still low, this is due to less meaningful mathematics learning. the learning of mathematics should be preceded by the introduction of problems appropriate to the student environment. The Contextual Teaching And Learning Approach (CTL) is a learning concept that can help teachers connect between the material they teach and the students' real-world situations and encourage them to make connections between the knowledge they possess and their real-world forwarding. The results showed that the Contextual Teacher and Learning approach did not affect the students' understanding of mathematical concepts in grade VII SMPN 26 Padang, because the experimental group did not differ from the control group. Keywords - understanding of mathematical concepts, Contextual Teaching And Learning Approach (CTL)